Scalable policy adoption and sustainable implementation of surgical care in the Americas - Nikathan Kumar; Gabriella Y. Hyman; Ayla Gerk; Taylor Wurdeman; Tarsicio Uribe-Leitz; Scott Corlew; Kee B. Park; John G. Meara; Robert Riviello; Emmanuel M. Makasa; Jimmy Kolker; Joanne Manrique; et al. (Revista Panamericana de Salud Pública)
On September 29, 2023, the Republic of Ecuador convened a meeting to address surgical system strengthening and urge political leaders to invest in surgical infrastructure. The meeting included experts in health diplomacy, innovative financing, implementation strategy and national surgical plans. The event occurred in parallel with the Sixtieth Directing Council of the Pan American Health Organization, Seventy-fifth session of the World Health Organization Regional Committee for the Americas. The meeting centered around four major areas: (i) building surgical capacity as a means to develop universal health care and emergency preparedness; (ii) developing policies and strategies for strengthening surgical systems; (iii) developing models for financing, sustaining, and improving surgical systems in low- and middle-income countries; and (iv) evaluating implementation strategies for funding these endeavors. National surgical plans represent a critical opportunity to build resilient health care systems by establishing comprehensive and sustainable policies. This article highlights the key messages from the event, which focused on Latin America, to inform the broader global health community.